Maternal and perinatal outcomes of minimally invasive fetal surgeries: experience from two reference centers in Rio de Janeiro, Brazil - Ávila, Luísa Moreira de; Carvalho, Paulo Roberto Nassar de; Sá, Renato Augusto Moreira de; Gomes Junior, Saint Clair; Araujo Júnior, Edward (São Paulo Medical Journal, 2025)
BACKGROUND: Concerns regarding high open surgery-related maternal morbidity have led to improvements in minimally invasive fetal surgeries. OBJECTIVE: To analyze the perinatal and maternal outcomes of minimally invasive fetal surgery performed in Rio de Janeiro, Brazil. DESIGN AND SETTING: Retrospective cohort study conducted in two tertiary reference centers. METHODS: This retrospective descriptive study was conducted using medical records from 2011 to 2019. The outcomes included maternal and pregnancy complications, neonatal morbidity, and mortality from the intrauterine period to hospital discharge. RESULTS: Fifty mothers and 70 fetuses were included in this study. The pathologies included twin-twin transfusion syndrome, congenital diaphragmatic hernia, myelomeningocele, lower urinary tract obstruction, pleural effusion, congenital upper airway obstruction syndrome, and amniotic band syndrome. Regarding maternal complications, 8% had anesthetic complications, 12% had infectious complications, and 6% required blood transfusions. The mean gestational age at surgery was 25 weeks, the mean gestational age at delivery was 33 weeks, 83% of fetuses undergoing surgery were born alive, and 69% were discharged from the neonatal intensive care unit. CONCLUSION: Despite the small sample size, we demonstrated that minimally invasive fetal surgeries are safe for pregnant women. Perinatal mortality and prematurity rates in this study were comparable to those previously. Prematurity remains the most significant problem associated with fetal surgery.